INTERNALISASI NILAI-NILAI RELIGIUS MELALUI PEMBIASAANDI SD ISLAM TERPADU KOTA MALANG - Elisa Ade Astarina; Kasuwi Saiban; Umi Salamah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to determine: (1) what values are internalized through habituation at SDIT Insan Permata Kota Malang. (2) the process of internalizing religious values through habituation at SDIT Insan Permata Kota Malang, (3) the impact of internalizing religious values through habituation at SDIT Insan Permata Kota Malang. This study uses a qualitative approach with a descriptive research type. This study shows that the religious values instilled in students include values derived from divine values, namely faith and piety, and values derived from human values, including brotherhood, compassion, trustworthiness, and generosity. The internalization process is divided into three stages, namely the value transformation stage, the value transaction stage, and the value transinternalization stage. The impact of the internalization of religious values through habit formation is that students have good religious values, as seen in their more orderly and proper worship, greater responsibility for their duties and obligations, and a growing habit of giving alms.